Teaching Composition to Bribri and Cabecar University Students: The Case of Disagreements - Serrato Pineda, Luis (2023)
This paper addresses the issue of disagreements present in academic texts written by university students from Bribri and Cabecar communities. Following the approaches on bilingualism (Baker, 1993), language contact (Palacios, 2011), and revision (Cassany, 2014), a 10-hour didactic proposal was designed and applied. Firstly, it aimed at raising awareness of the phenomenon of disagreement in varieties of Spanish in contact with Bribri and Cabecar, and, secondly, it promotes the recognition and review of these in academic texts. Moreover, it sought to generate awareness about some desirable characteristics in these writings. This research was raised after making a diagnosis, which showed that the productions written by these students tend to present a greater number of disagreements than those of speakers of historically monolingual communities in Spanish, both in rural and urban areas. An evaluation instrument applied at the beginning and at the end of a course-workshop showed a reduction in the number of disagreements in the revised and corrected texts, as well as a better understanding of important characteristics of the academic texts.